Prediction of Growth Characteristics and Migration Period of Spodoptera frugiperda (Lepidoptera: Noctuidae) According to Temperature - Seongkyun Lee; Younguk Park; Chohee Hwang; Areum Park; Seokho Lee; Juhyoung Kim (Insects, 2022)
In 2019, an outbreak of Spodoptera frugiperda (Smith) was first reported in Korea. This study aimed to determine the growth rate and feeding amount of S. frugiperda by temperature to establish the right time window for its control and management. Linear regression analysis was used to determine the growth period and thermal requirements of S. frugiperda. The longest growth period of 97.2 ± 1.2 days was observed at 16 °C, and the shortest growth period of 15.5 ± 0.7 days was observed at 36 °C. In terms of each growth stage, the pupal period was the longest at all temperatures, followed by the egg period. The maximum corn leaf feeding amount (6.61 g) was observed for the larvae grown at 16 °C, and the minimum (2.9 g) was observed at 36 °C. However, the daily feeding amount of S. frugiperda larvae was the highest at 28 °C and 32 °C. The hatching rate according to temperature exceeded 70% at 24 °C, 28 °C, and 32 °C, and the survival rate of larvae and pupae was 100% at 24 °C to 32 °C. Based on these results, a temperature range of 28 °C to 32 °C is proposed as the optimum temperature for the growth of S. frugiperda.